Fresno County Bar Association Judges' Dinner at Crossland's Barn with Bernie Witkin - Watkins, Howard::::::::: (1989)
Sal Sciandra shaking hands with Michael Berdinella; Juvenile Court Referee Phillip Silva smiling in background